Lady Whistledown strikes back - Quinn, Julia; Enoch, Suzanne; Hawkins, Karen; Ryan, Mia (Avon romance., 2022)
Who stole Lady Neeley's bracelet? Was it the fortune hunter, the gambler, the servant, or the rogue? All of London is abuzz with speculation, but it is clear that one of four couples is connected to the crime. And you'll hear it first from Lady Whistledown!